2019
DOI: 10.1097/prs.0000000000005076
|View full text |Cite
|
Sign up to set email alerts
|

Total Muscle Coverage versus AlloDerm Human Dermal Matrix for Implant-Based Breast Reconstruction

Abstract: Background: Prosthetic breast reconstruction is the most common method for treatment of patients undergoing mastectomy. Acellular dermal matrix has become more popular in implant-based breast reconstruction. Methods: The authors conducted a retrospective review of all patients undergoing prosthetic breast reconstruction between August of 2002 and December of 2013. Patients were analyzed in terms of demographics, fill volumes, number of expansions, costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The initial PubMed/MEDLINE search revealed 46 articles eligible for full-text review; of these, 12 were included in both the systematic review and meta-analysis. [11][12][13][14][15][16][17][18][19][20][21][22] Among these 12 studies, nine were retrospective chart reviews, two were prospective cohort studies, and one was a randomized trial ( Figure 1 ).…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…The initial PubMed/MEDLINE search revealed 46 articles eligible for full-text review; of these, 12 were included in both the systematic review and meta-analysis. [11][12][13][14][15][16][17][18][19][20][21][22] Among these 12 studies, nine were retrospective chart reviews, two were prospective cohort studies, and one was a randomized trial ( Figure 1 ).…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…For preservation of the IMF, it has been previously demonstrated in dual-plane reconstruction that less implant displacement occurs with ADM use; however, this difference was not statistically significant. 8,13 Pocket-defining sutures may play a similar role in this regard; however, there currently exists no evidence-based comparison between suture pocket-plasty and dermal substitutes for pocket contour. In the present cohort, ADM was used in 79% of patients, but was only wrapped anteriorly around implants and thus not truly used in a structural context for pocket control.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with the change in drain protocol, the switch of acellular dermal matrix from AlloDerm (sterility assurance level, 10 −3 ) to DermACELL (sterility assurance level, 10 −6 ) may have played a role in the reduction in the rate of infection. The use of acellular dermal matrix in breast reconstruction has been associated with higher rates of seroma and infection in some studies [26][27][28][29][30][31][32][33][34] ; however, others have found equivalent complication rates with and without the use of acellular dermal matrix. [35][36][37][38][39][40][41][42] Industry funding of research involving acellular dermal matrix in breast reconstruction may compromise reliability of results, and as in all of medicine, negative findings may be underpublished, biasing the available literature.…”
Section: Discussionmentioning
confidence: 99%